Neurologic symptoms following COVID-19 in Lima, Peru: a prospective longitudinal observational study - Huff, Hanalise V.; Villanueva-Colina, Carla; Diaz, Monica M.; Tovar, Sofia; Davila Luna, Andrea; Wu, Tianxia; Hamer, Davidson H.; Koralnik, Igor J.; Solomon, Tom; Caniza, Miguela A.; Garcia, Patricia J. (Frontiers in Neurology, 2025)
IntroductionThere is limited research on long-term neurologic symptoms following SARS-CoV-2 infection in Peru. This study aimed to describe the longitudinal experience of survivors of mild to moderate COVID-19 in Lima, Peru.MethodsThis prospective, longitudinal observational study included neurologic follow-up data between 3- and 12-months following SARS-CoV-2 infection. Recruitment to a parent study: “Natural History of SARS-CoV-2 in Comparison to Influenza Virus: A Multi-site Study Focused on the Southern Hemisphere and Equatorial Regions” (COFLU Peru), occurred between February 2021 and February 2022 in a Callao, Peru public hospital emergency department. In-person visits for this sub-study, “Neuro COFLU,” included neurologic history and symptom questionnaire.ResultsFifty-four patients were seen for at least one visit, two of whom required hospitalization for COVID-19. Forty-one (76%) reported at least one pre-existing neurologic diagnosis (59% headaches; 24% migraines). At follow-up visits, patients reported at least one new neurologic symptom since COVID-19: 24/29 (83%) at 90 days, 31/42 (74%) at 180 days, 41/46 (89%) at 270 days, and 20/21 (95%) at 365 days. The median number of new symptoms was 3 at 90 days, 3 at 180, 4 at 270 and 3 at 365 days. Days 90–180 frequent symptoms included: muscular pain, neck stiffness, headache, loss of appetite, numbness, insomnia, and weakness (24–31%). Days 181–365 frequent symptoms included: fatigue, weakness, memory problems, irritability, changes in hearing, muscular pain, joint pain, and insomnia (28–33%). Pre-existing anxiety was associated with post-COVID-19 hearing changes, muscular pain, numbness and weakness and pre-existing depression with neck stiffness and numbness. No significant association was found with age, sex, vaccination status, or pre-existing headaches. Full recovery was reported for 6/29 (21%) at day 90, 13/42 (31%) at day 180, 17/46 (37%) at day 270, and 9/20 (45%) at day 365. By day 365, patients reported median recovery of 85–90%.DiscussionPersistent neurological symptoms are common in COVID-19 survivors in Lima. Many new neurologic symptoms persisted and increased in prevalence over 3–12 months. Limitations include lack of control group and small sample size. Longitudinal studies of outcomes are needed to predict and mitigate the long-term physical, social and economic effects of SARS-CoV-2 infection.